Do employers prefer migrant workers? Evidence from a Chinese job board - Peter Kuhn; Kailing Shen (IZA Journal of Labor Economics, 2015)
We study urban, private sector Chinese employers' preferences between workers with and without a local permanent residence permit (hukou) using callback information from an Internet job board. We find that these employers prefer migrant workers to locals who are identically matched to the job's requirements; these preferences are strongest in jobs requiring lower levels of education and offering low pay. While migrant-native payroll tax differentials might account for some of this gap, we argue that the patterns are hard to explain without some role for a migrant productivity advantage in less skilled jobs. Possible sources of this advantage include positive selection of nonlocals into migration, negative selection of local workers into formal search for unskilled private sector jobs, efficiency wage effects related to unskilled migrants' limited access to the urban social safety net, and intertemporal labor and effort substitution by temporary migrants that makes them more desirable workers.
Keywords: O15; R23; 330; Temporary migration; China; Hukou; Personalbeschaffung; Arbeitsmigranten; Arbeitsproduktivität; China